EFFECTIVENESS OF WHATSAPP BOT-BASED EDUCATIONAL MEDIA AND LECTURES ON INCREASING MOTHER’S KNOWLEDGE ABOUT GASTROENTERITIS IN CHILDREN - Ar Royo, Sonia Puspita; Rohmah, Anis Ika Nur; Anggraini, Ika Rizki; Melliza, Nur (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Gastroenteritis is the main cause of death in children under five years of age with symptoms of dehydration, which causes high mortality rates. Gastroenteritis risk factors include poor hygiene, unclean water supplies, and lack of parental knowledge. Providing health education regarding gastroenteritis is very important to increase mother’s knowledge. WhatsApp bot and lectures are effective media that can be used in health education. Objectives: To determine the effectiveness of WhatsApp bot-based educational media and lectures in increasing knowledge of Gastroenteritis among housewives. Methods: The research method used was quasi-experimental using a two-group design posttest only. The research was conducted in Singosari, Malang, using two different groups with a sample size of 50. Group 01 was given education using WhatsApp bot media, while group 02 was given education using lecture media. The research data was tested using the Mann-Whitney test in SPSS version 25. Results: The demographic data obtained shows that the average number of respondents is (60%) not working or a housewife. The research results show a difference between giving education using the lecture method and WhatsApp bot media on housewives' knowledge level. Mother’s knowledge about gastroenteritis increased after being given education using two different media. The group using lecture media had a better increase in knowledge than the group using WhatsApp bot media. Conclusion: Health education regarding gastroenteritis based on lecture media is more effective than WhatsApp bot media in increasing mothers' knowledge about preventing gastroenteritis in children